PENGARUH PENGUNGKAPAN AKUNTANSI LINGKUNGAN DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2021-2023) - Maria Agustina Rau; Wilhelmina Mitan; Emilianus Eo Kutu Goo (Universitas Nusa Nipa Maumere, 2025)
This research aimed to examine the effect of environmental accounting disclosure and good corporate governance mechanisms on the financial performance of basic industry and chemical manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. This research used a quantitative causal approach with multiple linear regression data analysis to examine the relationship between environmental accounting disclosure and good corporate governance mechanisms (managerial ownership, institutional ownership, independent board of commissioners, and audit committee) on financial performance. The research data was obtained from secondary data in the form of financial reports and annual reports of the companies included in the sample. The results of this research indicated that, partially, environmental accounting disclosure did not have a significant effect on financial performance. Good corporate governance mechanisms, namely managerial ownership, institutional ownership, and independent boards of commissioners, did not have a significant effect on financial performance. Meanwhile, audit committees did not have a significant effect on financial performance. Simultaneously, environmental accounting disclosure and good corporate governance mechanisms had a significant effect on financial performance.